Anaphore Nominale Dans Des Récits Écrits Par Des Étudiants Ghanéens : Les Effets D’une Séquence Didactique - Kwawu, Alexander (European Scientific Journal, ESJ, 2018)
This paper assesses the impact of a sequence of didactic interventions on the use of nominal anaphors in a narrative text produced by Ghanaian university students of French as a foreign language. This study is necessitated by the lack of research investigating the effects of instruction on the use of cohesive devices in learner writing. 25 second-year students of the University of Cape Coast participated in a didactic sequence based on the types of nominal anaphors used in folktales. The impact of the teaching sequence was assessed by comparing the results obtained during the pretest with those of the post-test. The results showed improvements in students’use of nominal anaphoric resources. This was manifested in the increased diversification of lexical resources and the increased use of marked anaphoric expressions. These improvements show that the skilful usage of nominal anaphoric resources can be quickly developed in the frame of an adequate pedagogical intervention.